PENGGUNAAN MEDIA POSTER UNTUK MENINGKATKAN PEMAHAMAN MUFRADĀT DI SD MUHAMMADIYAH 1 SEDATI - Adib, Fathul; Fauji, Imam (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2024)
In Arabic language learning, the media used only focuses on books and is not diverse, which makes students less motivated to learn Arabic and less able to understand it, especially in understanding Arabic mufrodat in class. The learning media used by researchers as a strategy to overcome the problem of low understanding among students is poster media. This study aims to determine whether there is an increase or not related to the understanding of mufrodat in the use of poster media before and after being used in the classroom in Arabic language learning. This research was conducted using a quantitative approach with non-experimental designs. In this study obtained the results of the average value of pretest students 41.19 and the average value of posttest 81.83. In comparison to the average value of students, it can be seen that after being given treatment in the form of poster media, the value has increased by 40.64. The results of the paired sample test calculation using a 95% confidence level show that with a 2-tailed Sig value of 0.000 <0.05, there is a difference in pretest and posttest scores. Through these results and the value of the -t count < -t table with df = (n-1) of 62 (-36.007 < -1.998), it can be concluded that Ho is rejected, the accepted hypothesis is (Ha), and it can be concluded that "the use of poster media can improve the understanding of mufrodat of fifth grade students of SD Muhammadiyah 1 Sedati.”